Optimization of microalgae chlorella sp. and scenedesmus sp. at different growth parameters using design expert - Chen, Chian Xuan (2025)
Microalgae has been playing an important role in becoming an alternative energy source that is sustainable and capable in improving the environmental quality. This study was conducted to study the growth of locally isolated microalgae Chlorella sp. UKM 8 and Scenedesmus sp. UKM 9 at different growth parameters and to study the optimum condition from the selected parameter using the Design Expert Software. Two isolated microalgae species, Chlorella sp. UKM 8 and Scenedesmus sp. UKM 9, were successfully cultivated in Bold’s Basal Medium (BBM) under varying growth parameters, including light intensity, photoperiod, and pH, over a 10-day period. Thorough analysis of growth kinetics revealed that light availability significantly influenced the growth of both species. Under continuous darkness (0/24H photoperiod), both species experienced negative growth due to inhibited photosynthesis. Optimal growth rates were achieved under photoperiods of 12/12H and 24/0H, confirming their photoautotrophic nature. Chlorella sp. UKM 8 performed best in neutral conditions (pH 7), achieving a maximum growth rate of 0.4209 day-1 at a light intensity of 1500 lux. Scenedesmus sp. UKM 9 exhibited broader pH adaptability, with peak growth rates of 0.5238 day-1 at pH 7 and 0.5201 day-1 at pH 9 under 2000 lux. Optimization using Design Expert Software highlighted the significance of light intensity, photoperiod, and pH, with derived regression models accurately predicting growth conditions. The optimal parameters for Chlorella sp. UKM 8 were 1146.71 lux, 21.1811-hour photoperiod, and pH 7.7553, resulting in a maximum growth rate of 0.3039 day-1. For Scenedesmus sp. UKM 9, optimal growth occurred at 1910.26 lux, 12.204-hour photoperiod, and pH 7.8685, with a maximum growth rate of 0.3139 day-1. These findings provide valuable insights into optimizing cultivation parameters for enhanced biomass production.